Negative electrode active material, secondary battery, and electric device
By using silicon-carbon composite particles with different silicon contents, the problem of poor circulation stability of silicon-based negative electrode materials is solved, and a battery negative electrode material with high capacity and good circulation stability is achieved.
Patent Information
- Application Number
- CN202311639597.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-11-30
AI Technical Summary
The volume expansion rate of silicon-based negative electrode material is large during the circulation process, resulting in poor circulation stability and affecting the circulation performance of the battery.
A silicon-carbon composite material is used, including two silicon-carbon composite particles with different silicon content, to improve the capacity and cycle stability by adjusting the mass percentage of silicon elements and the pore structure of the carbon matrix.
It is achieved to improve the cycle stability of the silicon carbon negative electrode material while maintaining a high capacity, thereby improving the energy density and cycling performance of the battery.
Smart Images

Figure CN119833579A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode active material, a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application range of batteries represented by lithium-ion batteries has become more and more extensive, batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance. Silicon-based negative electrode materials are considered to be the best choice to meet the requirements of high energy density due to their high specific capacity.
[0003] However, the volume expansion rate of silicon-based negative electrode materials during the cycle process is large and the cycle stability is poor, which will lead to reduced battery cycle performance. Therefore, silicon-based negative electrode materials need to be further improved. Summary of the invention
[0004] The present application provides a negative electrode active material, a secondary battery and an electrical device. The silicon-carbon negative electrode material has a high gram capacity and good cycle stability.
[0005] In a first aspect, the present application provides a negative electrode active material, including a silicon-carbon composite material, wherein the silicon-carbon composite material includes a first silicon-carbon composite particle and a second silicon-carbon composite particle; the first silicon-carbon composite particle includes a first carbon matrix having a pore structure and a first silicon-based material arranged in the pore structure of the first carbon matrix; the second silicon-carbon composite particle includes a second carbon matrix having a pore structure and a second silicon-based material arranged in the pore structure of the second carbon matrix; and the mass percentage of silicon element in the first silicon-carbon composite particle is greater than the mass percentage of silicon element in the second silicon-carbon composite particle.
[0006] According to the present application, the negative electrode active material includes a silicon-carbon composite material, including two silicon-carbon composite particles with different silicon contents. The first silicon-carbon composite particles with a higher silicon content are beneficial to improving the gram capacity of the silicon-carbon negative electrode material, and the second silicon-carbon composite particles with a lower silicon content are beneficial to improving the cycle stability of the silicon-carbon negative electrode material. The two work together to enable the silicon-carbon composite material to have a higher gram capacity while having good cycle stability, thereby improving the energy density and cycle performance of the battery.
[0007] In some embodiments, the mass percentage of silicon in the first silicon-carbon composite particles is ≥50%, and may be 50%-60%; and / or the mass percentage of silicon in the second silicon-carbon composite particles is ≤47%, and may be 38%-47%. In this case, the silicon-carbon composite material as a whole has a higher gram capacity and better cycle stability.
[0008] In some embodiments, the mass percentage of silicon in the first silicon-carbon composite particle is ω1, the mass percentage of silicon in the second silicon-carbon composite particle is ω2, and the negative electrode active material satisfies: 1.06≤ω1 / ω2≤1.6, which can be 1.1-1.3. In this case, the silicon-carbon composite material as a whole has a higher gram capacity and better cycle stability.
[0009] In some embodiments, the first carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the first carbon matrix is V1≥0.6cm 3 / g, optional 0.6-0.75cm 3 / g; and / or, the second carbon matrix comprises a microporous structure, and the pore volume of the microporous structure in the second carbon matrix is V2≥0.4cm 3 / g, optional 0.5-0.7cm 3 / g. In this case, the first silicon-carbon composite particles and / or the second silicon-carbon composite particles have better cycle stability, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0010] In some embodiments, the first carbon matrix and the second carbon matrix both include a microporous structure, and the pore volume of the microporous structure in the first carbon matrix is greater than the pore volume of the microporous structure in the second carbon matrix. The first silicon-carbon composite particles and the second silicon-carbon composite particles have better cycle stability, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0011] In some embodiments, the average pore size of the pore structure in the first carbon matrix is d1≤5nm, which can be 1-4nm; and / or the average pore size of the pore structure in the second carbon matrix is d2≤10nm, which can be 3-5nm. Suitable pore size is conducive to reducing the volume change rate of the first silicon-carbon composite particle and / or the second silicon-carbon composite particle, and the cycle stability is better, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0012] In some embodiments, the average pore size of the pore structure in the first carbon matrix is smaller than the average pore size of the pore structure in the second carbon matrix. In this case, the first silicon-carbon composite particle has better cycle stability, and the second silicon-carbon composite particle can reserve a larger expansion space, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0013] In some embodiments, the specific surface area of the first carbon matrix is BET1 ≥ 1800 m 2 / g, optional 1800-2000m 2 / g; and / or, the specific surface area of the second carbon matrix is BET2≥1600m 2 / g, optional 1600-1800m 2 / g. At this time, the pore structure of the first carbon matrix and / or the second carbon matrix can accommodate more silicon-based materials, and the first silicon-carbon composite particles and the second silicon-carbon composite particles have better cycle stability, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0014] In some embodiments, the specific surface area of the first carbon matrix is greater than the specific surface area of the second carbon matrix. In this case, the first silicon-carbon composite particles have better cycle stability, and the structure of the second silicon-carbon composite particles is more stable, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0015] In some embodiments, based on the silicon-carbon composite material, the mass content of the first silicon-carbon composite particles is less than the mass content of the second silicon-carbon composite particles. In this case, the overall cycle stability of the silicon-carbon composite material is improved, further improving the cycle performance of the battery.
[0016] In some embodiments, based on the silicon-carbon composite material, the mass content of the first silicon-carbon composite particles is ≤10%, optionally 0.1%-5%; and / or, based on the silicon-carbon composite material, the mass content of the second silicon-carbon composite particles is ≥80%, optionally 80%-99.8%. At this time, the overall cycle stability of the silicon-carbon composite material further improves the cycle performance of the battery.
[0017] In some embodiments, at least part of the surface of the first silicon-carbon composite particle and / or the second silicon-carbon composite particle has a coating layer, and optionally, the coating layer is a carbon coating layer. In this case, the side reaction between the first silicon-carbon composite particle and / or the second silicon-carbon composite particle and the electrolyte is smaller, and the overall cycle stability of the silicon-carbon composite material is better, further improving the initial efficiency and cycle performance of the battery.
[0018] In some embodiments, the silicon-carbon composite material further includes a third silicon-carbon composite particle, the third silicon-carbon composite particle includes a third carbon matrix having a pore structure and a third silicon-based material disposed in the pore structure of the third carbon matrix, the mass percentage of silicon in the third silicon-carbon composite particle is less than the mass percentage of silicon in the first silicon-carbon composite particle, and the mass percentage of silicon in the third silicon-carbon composite particle is less than the mass percentage of silicon in the second silicon-carbon composite particle. The third silicon-carbon composite particle can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0019] In some embodiments, the silicon-carbon composite material further includes a third silicon-carbon composite particle, the first silicon-carbon composite particle includes a third carbon matrix having a pore structure and a third silicon-based material disposed in the pore structure of the third carbon matrix, the average pore size of the pore structure in the third carbon matrix is smaller than the average pore size of the pore structure in the first carbon matrix, and the average pore size of the pore structure in the third carbon matrix is smaller than the average pore size of the pore structure in the second carbon matrix. In this case, the processing performance of the silicon-carbon composite material can be improved, the compaction density of the negative electrode sheet can be increased, and the energy density of the battery can be increased.
[0020] In some embodiments, the silicon-carbon composite material further includes a third silicon-carbon composite particle, the first silicon-carbon composite particle includes a third carbon matrix having a pore structure and a third silicon-based material disposed in the pore structure of the third carbon matrix, the specific surface area of the third carbon matrix is smaller than the specific surface area of the first carbon matrix, and the specific surface area of the third carbon matrix is smaller than the specific surface area of the second carbon matrix. In this case, the processing performance of the silicon-carbon composite material can be improved, the compaction density of the negative electrode sheet can be increased, and the energy density of the battery can be increased.
[0021] In some embodiments, the third silicon-carbon composite particles satisfy at least one of the following conditions: 1) the mass percentage of silicon element in the third silicon-carbon composite particles is ≤25%, which can be 20%-25%; 2) the average pore size of the pore structure in the third carbon matrix is d3≤4nm, which can be 1-3nm; 3) the third carbon matrix contains micropores with a pore size of <2nm, wherein the percentage of micropore volume to total pore volume is p≥60%, which can be 70%-85%; 4) the powder compaction density of the third carbon matrix under a pressure of 49000N is 0.4-1.1g / cm 3 , preferably 0.4-0.8g / cm 3 ; 5) The specific surface area of the third carbon matrix BET3 ≥ 1000m 2 / g, preferably 1000-1300m 2 / g. At this time, the battery's energy density and cycle performance are better.
[0022] In some embodiments, at least one of the first silicon-based material, the second silicon-based material, or the third silicon-based material includes silicon grains; optionally, the grain size of the silicon grains is less than or equal to 10 nm. In this case, the volume change rate of the first silicon-carbon composite particles, the second silicon-carbon composite particles, or the third silicon-carbon composite particles is smaller, and the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0023] In some embodiments, the silicon-carbon composite material satisfies at least one of the following conditions: 1) the specific surface area of the silicon-carbon composite material is less than or equal to 6 m 2 / g, optional ≤4m 2 / g; 2) the volume average particle size Dv50 of the silicon-carbon composite material is 5-15μm, which can be 5-10μm; 3) based on the total mass of the silicon-carbon composite material, the mass percentage of silicon in the silicon-carbon composite material is 35%-50%, which can be 40%-50%; 4) the porosity of the silicon-carbon composite material is 45%-65%, which can be 45%-55%; 5) the powder compaction density of the silicon-carbon composite material under a pressure of 49000N is 0.8-1.2g / cm 3 , optional 0.9-1.1g / cm 3 ; 6) The tap density of the silicon-carbon composite material is 0.6-1.0g / cm 3 , optional 0.7-0.9g / cm 3 ; 7) The powder resistivity of the silicon-carbon composite material is ≤5Ω·cm, and can be ≤3Ω·cm; 8) (Dv90-Dv10) / Dv50 of the silicon-carbon composite material is ≤5, and can be ≤2.5. In this case, the energy density and cycle performance of the battery are better.
[0024] In a second aspect, the present application provides a secondary battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer, wherein the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises the silicon-carbon composite material described in any embodiment of the first aspect.
[0025] In a third aspect, the present application provides an electrical device, comprising the secondary battery described in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0027] Figure 2 yes Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0028] Figure 3is a schematic diagram of a battery module according to an embodiment of the present application.
[0029] Figure 4 is a schematic diagram of a battery according to one embodiment of the present application.
[0030] Figure 5 yes Figure 4 An exploded view of a battery according to an embodiment of the present application is shown.
[0031] Figure 6 It is a schematic diagram of an electrical device using a battery cell according to an embodiment of the present application as a power source.
[0032] Description of reference numerals:
[0033] 1 secondary battery; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly. DETAILED DESCRIPTION
[0034] Below, the embodiments of the silicon-carbon negative electrode material, negative electrode sheet, battery and electrical equipment of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0035] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0036] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0037] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0038] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0039] As described in the background technology above, silicon-based negative electrode materials have a high gram capacity, but their volume expansion rate during the cycle process is large, resulting in poor cycle stability and causing the cycle performance of the battery to deteriorate.
[0040] In this regard, the relevant technology will blend silicon-based negative electrode materials and carbon-based negative electrode materials with good cycle stability as negative electrode materials, or directly compound silicon-based negative electrode materials with carbon-based negative electrode materials as negative electrode materials. However, the problem is that as the silicon content in the above-mentioned negative electrode materials increases, the cycle performance of the battery also decreases. Therefore, it is difficult to obtain a battery that takes into account both energy density and cycle performance.
[0041] Based on this, the present application provides a negative electrode active material having high gram capacity and cycle stability, which can be applied to batteries to effectively improve the energy density and cycle performance of the batteries. The specific implementation methods of the present application are described in detail below.
[0042] Negative electrode active material
[0043] In a first aspect, the present application provides a negative electrode active material, including a silicon-carbon composite material, the silicon-carbon composite material including a first silicon-carbon composite particle and a second silicon-carbon composite particle; the first silicon-carbon composite particle includes a first carbon matrix having a pore structure and a first silicon-based material arranged in the pore structure of the first carbon matrix; the second silicon-carbon composite particle includes a second carbon matrix having a pore structure and a second silicon-based material arranged in the pore structure of the second carbon matrix; and the mass percentage of silicon element in the first silicon-carbon composite particle is greater than the mass percentage of silicon element in the second silicon-carbon composite particle.
[0044] According to the present application, the negative electrode active material includes a silicon-carbon composite material, which includes two carbon-silicon composite particles with different silicon contents. Both silicon-carbon composite particles include a carbon matrix and a silicon-based material arranged in the pore structure of the carbon matrix. It can be understood that although the silicon-based material has a large volume change rate during the charge and discharge process, the pore structure of the carbon matrix can limit the impact of its volume change on the overall volume of the silicon-carbon composite particles, so that the two silicon-carbon composite particles have a smaller volume change rate, thereby the silicon-carbon composite material has better cycle stability, which is beneficial to improving the cycle performance of the battery; on the other hand, the mass percentage of silicon element in the two silicon-carbon composite particles is different. The first silicon-carbon composite particle The mass percentage of silicon element in the first silicon-carbon composite particle is greater than the mass percentage of silicon element in the second silicon-carbon composite particle, so the gram capacity of the first silicon-carbon composite particle is higher, thereby improving the overall gram capacity of the silicon-carbon composite material, and the volume change rate of the second silicon-carbon composite particle during the charge and discharge process is smaller. When the two are mixed, space for the volume change of the first silicon-carbon composite particle can be reserved, thereby reducing the extrusion between particles of the silicon-carbon negative electrode material during the charge and discharge process, alleviating particle breakage caused by volume expansion, and then effectively improving the overall cycle stability of the silicon-carbon composite material. Therefore, using the silicon-carbon composite material as the negative electrode active material can improve the energy density and cycle performance of the battery.
[0045] It should also be noted that the first silicon-carbon composite particle and the second silicon-carbon composite particle are two different silicon-carbon composite particles. Although the two are distinguished only by the silicon content, generally speaking, in the silicon-carbon composite material, the difference between the mass percentage of silicon in the first silicon-carbon composite particle and the mass percentage of silicon in the second silicon-carbon composite particle is not less than 0.5%. Prior to the present application, carbon-silicon composite particles have been used as negative electrode active materials, but usually a silicon-carbon composite particle is used as the negative electrode active material, and silicon-carbon composite particles with a certain silicon content can be prepared by known methods (such as vapor deposition method, etc.). Although the carbon-silicon composite particles prepared under the same conditions may still have certain differences in the content of silicon in the carbon-silicon composite particles actually obtained, the difference is small and is not enough to distinguish them as two different silicon-carbon composite particles, and cannot meet the requirements of the implementation method of the present application.
[0046] In some embodiments, the mass percentage of silicon in the first silicon-carbon composite particles is ≥50%; and / or the mass percentage of silicon in the second silicon-carbon composite particles is ≤47%.
[0047] In some of the above embodiments, the mass percentage of silicon in the first silicon-carbon composite particles is not less than 50%, that is, the first silicon-carbon composite particles have a higher gram capacity, which is conducive to further improving the energy density of the battery. For example, the mass percentage of silicon in the first silicon-carbon composite particles can be 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, or within the range of any of the above values. Further, the mass percentage of silicon in the first silicon-carbon composite particles can be 50%-60%, at which time the first silicon-carbon composite particles have better stability and are not prone to rupture during the charge and discharge process, which can further improve the cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0048] The mass percentage of silicon in the second silicon-carbon composite particles does not exceed 47%. At this time, the volume change rate of the second silicon-carbon composite particles during the charge and discharge process is small, and more space can be reserved to adapt to the volume change of the first silicon-carbon composite particles, so as to alleviate the mutual extrusion of the silicon-carbon composite materials during the charge and discharge process, thereby improving the overall cycle stability of the silicon-carbon composite materials and further improving the cycle performance of the battery. For example, the mass percentage of silicon in the second silicon-carbon composite particles can be 47%, 46%, 45%, 44%, 43%, 42%, 41%, 40%, 39%, 38%, 37%, 36%, 35%, or within the range of any of the above values. Further, the mass percentage of silicon in the second silicon-carbon composite particles can be 38%-47%. At this time, the second silicon-carbon composite particles have a higher gram capacity, which is beneficial to improve the energy density of the battery.
[0049] In some embodiments, the mass percentage of silicon in the first silicon-carbon composite particle is denoted as ω1, the mass percentage of silicon in the second silicon-carbon composite particle is denoted as ω2, and the negative electrode active material satisfies: 1.06≤ω1 / ω2≤1.6.
[0050] In some of the above embodiments, the relationship between the mass percentage of silicon in the first silicon-carbon composite particle and the second silicon-carbon composite particle is further defined. It can be understood that in the silicon-carbon composite material, the two silicon-carbon composite particles can cooperate with each other to make the silicon-carbon composite material as a whole take into account both higher gram capacity and cycle stability. When the negative electrode active material satisfies: 1.06≤ω1 / ω2≤1.6, the force of the two particles squeezing each other during the charge and discharge process can be further alleviated, thereby ensuring the stability of the particles. At the same time, the silicon-carbon composite material takes into account the higher gram capacity, further improving the energy density and cycle performance of the battery. For example, ω1 / ω2 can be 1.06, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55, 1.6, or within the range of any of the above values. Further, ω1 / ω2 can be 1.1-1.3, at which time the silicon-carbon composite material as a whole has a higher gram capacity and better cycle stability, and the energy density and cycle performance of the battery are better.
[0051] In some embodiments, the first carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the first carbon matrix is V1 ≥ 0.6 cm 3 / g; and / or, the second carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the second carbon matrix is V2≥0.4cm 3 / g, optional 0.5-0.7cm 3 / g.
[0052] In some of the above embodiments, the first carbon matrix includes a microporous structure, and the pore volume of the microporous structure is V1≥0.6cm 3 / g, it can be understood that the micropores have a content known in the art, which refers to pores with a diameter of less than 2nm. At the same time, according to the pore size of the pores, the pores can also be divided into mesopores and macropores, where the pore size of the mesopores is 2-50nm, and the pore size of the macropores is greater than 50nm. The particle size of the first silicon-based material in the microporous structure is smaller, and the first silicon-based material with a smaller particle size has a smaller volume change rate during the charging and discharging process. Therefore, the larger the pore volume of the microporous structure, the better the cycle stability of the first silicon-carbon composite particles, which can further improve the overall cycle stability of the silicon-carbon composite material, and the cycle performance of the battery is better. For example, the pore volume V1 of the microporous structure in the first carbon matrix can be 0.6cm 3 / g,0.62cm 3 / g,0.64cm 3 / g,0.65cm 3 / g, 0.67cm 3 / g,0.69cm 3 / g,0.7cm 3 / g,0.72cm 3 / g,0.74cm 3 / g, 0.75cm 3 / g, 0.77cm 3 / g,0.8cm 3 / g, or any of the above values. Further, the pore volume V1 of the microporous structure in the first carbon matrix can be 0.6-0.75 cm 3 / g, at this time, more first silicon-based materials are arranged in the microporous structure, the first silicon-carbon composite particles have better cycle stability, and the silicon-carbon composite material as a whole has better cycle stability, which further improves the cycle performance of the battery.
[0053] Likewise, the second carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the second carbon matrix is V2 ≥ 0.4 cm 3 / g, the first silicon-carbon composite particles have better cycle stability, further improving the overall cycle stability of the silicon-carbon composite material, and the cycle performance of the battery is better. For example, the pore volume V2 of the microporous structure in the second carbon matrix can be 0.4 cm 3 / g,0.42cm 3 / g, 0.45cm 3 / g,0.48cm 3 / g,0.5cm 3 / g,0.52cm 3 / g,0.55cm 3 / g,0.58cm 3 / g,0.6cm 3 / g,0.62cm 3 / g, 0.65cm 3 / g,0.69cm 3 / g,0.7cm 3 / g,0.72cm 3 / g,0.74cm 3 / g, 0.75cm 3 / g, or any of the above values. Further, the pore volume V2 of the microporous structure in the second carbon matrix can be 0.5-0.7 cm 3 / g, at this time the silicon-carbon composite material as a whole has better cycle stability, further improving the cycle performance of the battery.
[0054] In some embodiments, both the first carbon matrix and the second carbon matrix include a microporous structure, and the pore volume of the microporous structure in the first carbon matrix is greater than the pore volume of the microporous structure in the second carbon matrix.
[0055] In some of the above-mentioned embodiments, the first carbon matrix and the second carbon matrix both include a microporous structure. At this time, the first silicon-carbon composite particles and the second silicon-carbon composite particles both have good cycle stability. At the same time, the silicon content in the first silicon-carbon composite particles is higher than that in the second silicon-carbon composite particles. A larger pore volume of the microporous structure is required to allow the silicon-based material to be disposed in the microporous structure, thereby improving the cycle stability of the silicon-carbon composite particles. As a result, the pore volume of the microporous structure in the first carbon matrix is greater than the pore volume of the microporous structure in the second carbon matrix, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0056] In some embodiments, the average pore size of the pore structure in the first carbon matrix is d1≤5nm, optionally 1-4nm; and / or the average pore size of the pore structure in the second carbon matrix is d2≤10nm, optionally 3-5nm.
[0057] In some of the above embodiments, the average pore size d1 of the pore structure in the first carbon matrix does not exceed 5nm. It can be understood that the smaller the average pore size of the pore structure in the first carbon matrix, the smaller the average particle size of the first silicon-based material in the pore structure, so that the volume change rate of the first silicon-based material during the charge and discharge process is smaller, and the cycle stability of the first silicon-carbon composite particles is better, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery. For example, the average pore size d1 of the pore structure in the first carbon matrix can be 5nm, 4.5nm, 4nm, 3.5nm, 3nm, 2.5nm, 2nm, 1.5nm, 1nm, or within the range composed of any of the above values. Further, the average pore size d1 of the pore structure in the first carbon matrix can be 1-4nm, at which time the cycle stability of the first silicon-carbon composite particles is better, and the silicon-carbon composite material as a whole has better cycle stability, further improving the cycle performance of the battery.
[0058] Similarly, the average pore size d2 of the pore structure in the second carbon matrix does not exceed 10nm. At this time, the volume change rate of the second silicon-based material during the charge and discharge process is smaller, and the cycle stability of the second silicon-carbon composite particles is better, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery. For example, the average pore size d2 of the pore structure in the second carbon matrix can be 10nm, 9.5nm, 9nm, 8.5nm, 8nm, 7.5nm, 7nm, 6.5nm, 6nm, 5.5nm, 5nm, 4.5nm, 4nm, 3.5nm, 3nm, or within the range composed of any of the above values. Further, the average pore size d2 of the pore structure in the second carbon matrix can be 3-4nm, at this time, the cycle stability of the second silicon-carbon composite particles is better, and the silicon-carbon composite material as a whole has better cycle stability, further improving the cycle performance of the battery.
[0059] In some embodiments, an average pore size of the pore structure in the first carbon matrix is smaller than an average pore size of the pore structure in the second carbon matrix.
[0060] In some of the above-mentioned embodiments, since the mass percentage of silicon element in the first silicon-carbon composite particles is higher than that in the first silicon-carbon composite particles, the average pore size of the pore structure of the first carbon matrix can be further reduced to reduce the volume change rate of the first silicon-carbon composite particles and improve their cycle stability. At the same time, it can be understood that the second carbon matrix with a larger average pore size is not easy to break during the extrusion process, so that it can better adapt to the volume expansion of the first silicon-carbon composite particles, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery.
[0061] In some embodiments, the specific surface area of the first carbon substrate is BET1 ≥ 1800 m 2 / g, optional 1800-2000m 2 / g; and / or, the specific surface area of the second carbon matrix is BET2≥1600m 2 / g, optional 1600-1800m 2 / g.
[0062] In some of the above embodiments, the specific surface area BET1 of the first carbon matrix may be not less than 1800 m 2 / g, at this time, the pore structure of the first carbon matrix has enough space to accommodate more first silicon-based materials. On the one hand, the particle size of the first silicon-based material in the pore structure is limited by the pore structure, and on the other hand, the effect of the volume expansion of the first silicon-based material on the first silicon-carbon composite particles can be limited, so that the first silicon-carbon composite particles have a higher gram capacity and better cycle stability. For example, the specific surface area BET1 of the first carbon matrix can be 18001800m 2 / g, 1850m 2 / g,1900m 2 / g,1950m 2 / g,2000m 2 / g,2050m 2 / g,2100m 2 / g,2200m 2 / g,2300m 2 / g,2400m 2 / g, or within the range of any of the above values. Further, the specific surface area BET1 of the first carbon matrix can be 1800-2000m 2 / g, at this time, the first silicon-carbon composite particles have better cycle stability, and the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0063] Similarly, the specific surface area BET2 of the second carbon matrix may be not less than 1600 m 2 / g, the second silicon-carbon composite particles have better cycle stability, and the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery. For example, the specific surface area BET2 of the second carbon matrix can be 1600m 2 / g,1650m 2 / g,1700m 2 / g,1750m 2 / g,1800m 2 / g, 1850m 2 / g,1900m 2 / g,2000m 2 / g,2100m 2 / g,2200m 2 / g, or within the range of any of the above values. Preferably, the specific surface area BET2 of the second carbon matrix can be 1600-1800m 2 / g, at this time, the second silicon-carbon composite particles have better cycle stability, and the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0064] In some embodiments, the specific surface area of the first carbon substrate is greater than the specific surface area of the second carbon substrate.
[0065] In some of the above-mentioned embodiments, the mass percentage of silicon element in the first silicon-carbon composite particles is higher than that in the second silicon-carbon composite particles. The larger specific surface area of the first carbon matrix is conducive to the arrangement of the silicon-based material in the pore structure, so that the first silicon-carbon composite particles have better cycle stability. The smaller specific surface area of the second carbon matrix is conducive to improving the stability of the second silicon-carbon composite particle structure. At this time, the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0066] In some embodiments, based on the silicon-carbon composite material, the mass content of the first silicon-carbon composite particles is ≤10%, optionally 0.1%-5%; and / or, based on the silicon-carbon composite material, the mass content of the second silicon-carbon composite particles is ≥80%, optionally 80%-99.8%.
[0067] In some of the above embodiments, the mass content of the first silicon-carbon composite particles does not exceed 10%. Due to the high silicon content, the volume expansion rate is large during the charge and discharge process. At this time, the overall cycle stability of the silicon-carbon composite particles is better, and the overall gram capacity of the silicon-carbon composite particles can be improved to a certain extent, so as to better balance the energy density and cycle performance of the battery. For example, the mass content of the first silicon-carbon composite particles can be 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.1%, or within the range of any of the above values. Further, the mass content of the first silicon-carbon composite particles can be 0.1%-5%. At this time, the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0068] The mass content of the second silicon-carbon composite particles is not less than 80%. Since the silicon content is relatively small, the volume expansion rate is small during the charge and discharge process, and the second silicon-carbon composite particles can be used as the main material of the silicon-carbon composite material. At the same time, the second silicon-carbon composite particles can better adapt to the volume changes of the first silicon-carbon composite particles, improve the overall cycle stability of the silicon-carbon composite particles, and further improve the cycle performance of the battery. For example, the mass content of the second silicon-carbon composite particles can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.8% or any of the above values. Further, the mass content of the second silicon-carbon composite particles can be 80%-99.8%, at which time the overall cycle stability of the silicon-carbon composite material is better, further improving the cycle performance of the battery.
[0069] In some embodiments, at least a portion of the surface of the first silicon-carbon composite particle and / or the second silicon-carbon composite particle has a coating layer.
[0070] In some of the above embodiments, at least part of the surface of the first silicon-carbon composite particles and / or the second silicon-carbon composite particles has a coating layer, and the coating layer located on the surface can reduce the specific surface area of the carbon matrix, reduce the side reaction with the electrolyte, and further improve the initial efficiency and cycle performance of the battery. It should be noted that after the first silicon-carbon composite particles and / or the second silicon-carbon composite particles are carbon-coated, the mass percentage of silicon in the first silicon-carbon composite particles will be reduced to a certain extent, but the effect is small and will not significantly change the mass percentage of silicon in the silicon-carbon composite particles. Furthermore, the coating layer is a carbon coating layer, which has good conductivity and stability and will not significantly affect the electrical properties of the silicon-carbon composite material.
[0071] In some embodiments, the silicon-carbon composite material also includes third silicon-carbon composite particles, the third silicon-carbon composite particles include a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the mass percentage of silicon element in the third silicon-carbon composite particles is less than the mass percentage of silicon element in the first silicon-carbon composite particles, and the mass percentage of silicon element in the third silicon-carbon composite particles is less than the mass percentage of silicon element in the second silicon-carbon composite particles.
[0072] In some of the above-mentioned embodiments, the silicon-carbon composite material also includes a third silicon-carbon composite particle, in which the mass percentage of silicon element is less than that of the first silicon-carbon composite particle and the second silicon-carbon composite particle. Therefore, its volume change rate during the charging and discharging process is smaller. In the mixed system of the silicon-carbon composite material, more space for the expansion of the silicon-carbon composite particles can be reserved, thereby alleviating the extrusion between the composite particles, further improving the overall cycle stability of the silicon-carbon composite material, and then improving the cycle performance and energy density of the battery.
[0073] In some embodiments, the silicon-carbon composite material also includes a third silicon-carbon composite particle, the first silicon-carbon composite particle includes a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the average pore size of the pore structure in the third carbon matrix is smaller than the average pore size of the pore structure in the first carbon matrix, and the average pore size of the pore structure in the third carbon matrix is smaller than the average pore size of the pore structure in the second carbon matrix.
[0074] In some of the above embodiments, the average pore size of the pore structure in the third carbon matrix is smaller than the average pore size of the pore structure in the first carbon matrix and the second carbon matrix. The smaller average pore size can make the third carbon matrix have higher strength, which can improve the overall processability of the silicon-carbon composite material, and is not prone to rupture during the production process, and can increase the compaction density of the negative electrode sheet, thereby improving the energy density of the battery. In addition, higher strength and smaller volume expansion rate can also improve the overall cycle stability of the silicon-carbon composite material, thereby improving the cycle performance of the battery.
[0075] In some embodiments, the silicon-carbon composite material also includes third silicon-carbon composite particles, the first silicon-carbon composite particles include a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the specific surface area of the third carbon matrix is smaller than the specific surface area of the first carbon matrix, and the specific surface area of the third carbon matrix is smaller than the specific surface area of the second carbon matrix.
[0076] In some of the above-mentioned embodiments, the specific surface area of the third carbon matrix is smaller than the specific surface areas of the first carbon matrix and the second carbon matrix. Since the mass percentage of silicon element in the third silicon-carbon composite particles is relatively small compared with the first silicon-carbon composite particles and the second silicon-carbon composite particles, the specific surface area of the third carbon matrix can be appropriately reduced. A smaller specific surface area can increase the strength of the third silicon-carbon composite particles, thereby improving the processing performance of the silicon-carbon composite material, increasing the compaction density of the negative electrode sheet, and helping to increase the energy density of the battery.
[0077] In some embodiments, the mass percentage of silicon in the third silicon-carbon composite particles is ≤25%, and can be optionally 20-25%. At this time, the third silicon-carbon composite particles have a smaller volume change rate during the charge and discharge process, which can further improve the overall cycle stability of the silicon-carbon composite material. For example, the mass percentage of silicon in the third silicon-carbon composite particles can be 25%, 24%, 23%, 22%, 21%, 20%, 19%, 18%, 17%, 16%, 15%, 14%, 13%, 12%, 11%, 10%, or within the range composed of any of the above values. Further, the mass percentage of silicon in the third silicon-carbon composite particles can be 20%-25%, which can better take into account the overall gram capacity of the silicon-carbon composite material, which is beneficial to improve the energy density of the battery.
[0078] In some embodiments, the average pore size of the pore structure in the third carbon matrix is d3≤4nm, which can be selected as 1-3nm. At this time, the third silicon-carbon composite particles have a higher strength, which can make the silicon-carbon composite material as a whole have good processability, and can improve the compaction density of the negative electrode plate, thereby improving the energy density of the battery. At the same time, the smaller pore size is conducive to limiting the expansion of the volume of the third silicon-based material, so that the third silicon-carbon composite particles have good cycle stability, thereby improving the overall cycle stability of the silicon-carbon composite material and improving the battery cycle performance. For example, the average pore size d3 of the pore structure in the third carbon matrix can be 4nm, 3.5nm, 3nm, 2.5nm, 2nm, 1.5nm, 1nm, or within the range composed of any of the above values. Further, the average pore size of the pore structure in the third carbon matrix can be 1-3nm, which can further improve the energy density and cycle performance of the battery.
[0079] In some embodiments, the third carbon matrix contains micropores with a pore size of less than 2 nm, wherein the percentage of micropore volume in the total pore volume p ≥ 60%, which can be selected as 70%-85%. Since the micropores will not significantly reduce the strength of the particles, the third silicon-carbon composite material has a higher strength while retaining a higher porosity, which can alleviate the cracking of the silicon-carbon negative electrode material during the cold pressing process, thereby improving the processability of the silicon-carbon composite material, which is beneficial to improving the energy density of the battery; at the same time, most of the third silicon-based material is arranged in the micropores, which is beneficial to reduce the volume change rate of the third silicon-carbon composite particles, thereby improving the cycle performance of the battery. For example, the percentage p of the micropore volume in the third carbon matrix to the total pore volume can be 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or within the range composed of any of the above values. Further, p can be 70%-85%, at which time the energy density and cycle performance of the battery can be further improved.
[0080] In some embodiments, the powder compaction density of the third carbon matrix under a pressure of 49000N is 0.4-1.1 g / cm 3 , preferably 0.4-0.8g / cm 3 At this time, the third silicon-carbon composite material has a higher strength, which can alleviate the cracking of the silicon-carbon composite material during the cold pressing process, thereby improving the processability of the silicon-carbon composite material and helping to increase the energy density of the battery. For example, the powder compaction density of the third carbon matrix under a pressure of 49000N can be 0.4g / cm 3 , 0.5g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 , or any of the above values. Further, the powder compaction density of the third carbon matrix under a pressure of 49000N is 0.4-0.8g / cm 3 , at this time the energy density of the battery can be further improved.
[0081] In some embodiments, the specific surface area of the third carbon matrix BET3 ≥ 1000 m 2 / g, preferably 1000-1300m 2 / g. At this time, the pore structure of the third carbon matrix can accommodate more third silicon particles, and the stability of the third silicon-based material in the pore structure is better, so the cycle stability of the third silicon-carbon composite particles is better, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery. For example, the specific surface area BET3 of the third carbon matrix can be 1000m 2 / g,1050m 2 / g,1100m 2 / g, 1150m 2 / g,1200m 2 / g,1250m 2 / g,1300m 2 / g,1400m 2 / g,1500m 2 / g,1600m 2 / g, or within the range of any of the above values. The specific surface area BET3 of the third carbon matrix can be 1000-1300m 2 / g, at this time, the third silicon-carbon composite particles have better processability and can improve the energy density of the battery.
[0082] In some embodiments, at least one of the first silicon-based material, the second silicon-based material, or the third silicon-based material includes silicon grains. Since silicon grains have a higher gram capacity in silicon-based materials, the silicon-carbon composite material as a whole has a higher gram capacity at this time, which can further improve the energy density of the battery; in addition, since the silicon grains are arranged in the pore structure of the carbon matrix, the volume expansion of the silicon grains can be effectively limited, so that the silicon grains will not significantly affect the overall cycle stability of the silicon-carbon composite material. Further, the grain size of the silicon grains is less than or equal to 10nm. Since the smaller the grain size of the silicon particles, the smaller its anisotropy, the volume expansion rate of the silicon grains with charge and discharge is lower at this time, so that the first silicon-carbon composite particles, the second silicon-carbon composite particles, or the third silicon-carbon composite particles have better cycle stability, which can further improve the overall cycle stability of the silicon-carbon composite material and further improve the cycle performance of the battery. For example, the grain size of the silicon grains can be 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, or within the range of the composition described by any of the above values.
[0083] In some of the above embodiments, at least part of the surface of the third silicon-carbon composite particle has a coating layer, and the coating layer located on the surface can reduce the specific surface area of the carbon matrix, reduce the side reaction with the electrolyte, and further improve the initial efficiency and cycle performance of the battery. It should be noted that the carbon coating of the third silicon-carbon composite particle will reduce the mass percentage of silicon in the first silicon-carbon composite particle to a certain extent, but the effect is small and will not significantly change the mass percentage of silicon in the silicon-carbon composite particle. Furthermore, the coating layer is a carbon coating layer, which has good conductivity and stability and will not significantly affect the electrical properties of the silicon-carbon composite material.
[0084] In some embodiments, the specific surface area of the silicon-carbon composite material is ≤ 6 m 2 / g. Since silicon particles easily react with electrolyte to form solid electrolyte membrane, they will consume active ions in the electrolyte. At the same time, the volume expansion of silicon particles will cause the solid electrolyte membrane to be damaged, and then further react with the electrolyte. The specific surface area of silicon-carbon composite materials should be controlled to be no more than 6m 2 / g, the contact area between the silicon-carbon composite material and the electrolyte in the battery is smaller, reducing the loss of active ions and reducing side reactions, which can further improve the initial efficiency and cycle performance of the battery. For example, the specific surface area of the silicon-carbon composite material can be 1m 2 / g,2m 2 / g,3m 2 / g,4m 2 / g,5m 2 / g,6m 2 / g, or within the range of the composition described by any of the above values. Further, the specific surface area of the silicon-carbon composite material is ≤4m 2 / g, at this time the battery's first efficiency and cycle performance are better.
[0085] In some embodiments, the volume average particle size Dv50 of the silicon-carbon composite material is 5-15 μm. Because the particle size of the silicon-carbon composite material will affect the extraction / embedding of active ions and has a certain influence on the specific surface area. The volume average particle size Dv50 of the silicon-carbon composite material is controlled to be 5-15 μm. At this time, the silicon-carbon composite material is easier for the extraction / embedding of active ions, has better kinetic properties, and can further improve the cycle performance of the battery. For example, the Dv50 of the silicon-carbon composite material can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or within the range of the composition described by any of the above values. Further, the Dv50 of the silicon-carbon composite material is 5-10 μm, and the cycle performance of the battery is better.
[0086] In some embodiments, the mass percentage of silicon in the silicon-carbon composite material is 35%-50%. Generally, the higher the silicon content, the greater the gram capacity of the silicon-carbon composite material, and the worse the corresponding cycle stability. The mass percentage of silicon in the silicon-carbon composite material is controlled to be 35%-50%. At this time, the silicon-carbon composite material can better balance the gram capacity and cycle stability, and further improve the energy density and cycle performance of the battery. For example, the mass percentage of silicon in the silicon-carbon composite material can be 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or within the range of the composition described by any of the above values. Further, the mass percentage of silicon in the silicon-carbon composite material is 40%-50%, at which time the energy density and cycle performance of the battery are better.
[0087] In some embodiments, the porosity of the silicon-carbon composite material is 45%-65%. Since silicon particles expand greatly during the cycle, in order to reduce the volume expansion rate of the negative electrode sheet during the cycle and improve the cycle stability of the silicon-carbon composite material, the silicon-carbon composite material should have a suitable porosity to reserve space for the expansion of silicon particles, and relieve the stress generated by silicon expansion inside the silicon-carbon composite material, thereby improving the cycle performance of the battery; in addition, appropriate porosity can increase the compaction density of the negative electrode sheet and improve the energy density of the battery. For example, the porosity of the silicon-carbon composite material can be 45%, 47%, 49%, 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, or within the range of the composition described by any of the above values. Further, the porosity of the silicon-carbon composite material can be 45%-55%, at which time the energy density and cycle performance of the battery are better.
[0088] In some embodiments, the powder compaction density of the silicon-carbon composite material under a pressure of 49000N is 0.8-1.2 g / cm 3 , optional 0.9-1.1g / cm 3 At this time, the silicon-carbon composite material has better processability, which is conducive to improving the compaction density of the negative electrode sheet, thereby increasing the energy density of the battery. For example, the powder compaction density of the silicon-carbon composite material under a pressure of 49000N can be 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.00g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , or within the range of the composition described by any of the above values. Further, the powder compaction density of the silicon-carbon composite material under a pressure of 49000N can be 0.9-1.1g / cm 3 , at this time the energy density of the battery can be further improved.
[0089] In some embodiments, the tap density of the silicon-carbon composite material is 0.6-1.0 g / cm 3 , optional 0.7-0.9g / cm 3 At this time, the silicon-carbon composite material has better processability, which is conducive to improving the compaction density of the negative electrode sheet, thereby increasing the energy density of the battery. For example, the tap density of the silicon-carbon composite material can be 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3, 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1g / cm 3 , or within the range of the composition described by any of the above values. Further, the tap density of the silicon-carbon composite material can be 0.7-0.9 g / cm 3 , at this time the energy density of the battery can be further improved.
[0090] In some embodiments, the powder resistivity of the silicon-carbon composite material is ≤5Ω·cm. At this time, the silicon-carbon composite material has better conductivity, so that the gram capacity of the silicon-carbon composite material can be fully utilized, thereby further improving the energy density and cycle performance of the battery. For example, the powder resistivity of the silicon-carbon composite material can be 5Ω·cm, 4.5Ω·cm, 4Ω·cm, 3.5Ω·cm, 3Ω·cm, 2.5Ω·cm, 2Ω·cm, 1.5Ω·cm, 1Ω·cm, 0.5Ω·cm, or within the range of the composition described by any of the above values. Further, the powder resistivity of the silicon-carbon composite material can be ≤3Ω·cm, at which time the energy density and cycle performance of the battery are better.
[0091] In some embodiments, (Dv90-Dv10) / Dv50 of the silicon-carbon composite material is ≤5. At this time, the particle size distribution of the silicon-carbon composite material is in a narrow range, which can increase the porosity of the negative electrode film layer in the negative electrode sheet, thereby alleviating the extrusion of the silicon-carbon composite material during the charge and discharge process and improving the cycle performance of the battery. For example, (Dv90-Dv10) / Dv50 of the silicon-carbon composite material can be 5, 4, 3, 2, 1, or within the range of the composition described by any of the above values. Furthermore, (Dv90-Dv10) / Dv50 of the silicon-carbon composite material can be ≤3, in which case the cycle performance of the battery is better.
[0092] In the context of the present application, the mass percentages of the first silicon-carbon composite particles, the second silicon-carbon composite particles and the third silicon-carbon composite particles in the silicon-carbon composite material have meanings well known in the art and can be detected by known methods.
[0093] The grain size of silicon grains has a well-known meaning in the art and can be detected by known methods. For example, the XRD pattern of the sample is tested according to the JIS / K0131-1996 test standard. According to the XRD pattern of the sample, the half-peak width β and the diffraction angle θ of the Si (111) crystal plane are respectively taken and substituted into the Debye-Scherrer formula to calculate the grain size of the silicon particles.
[0094] Debye-Scherrer formula: Dhkl=kλ / βcosθ;
[0095] Dhkl——grain size, unit: nm; k——Scherrer constant, 0.89; λ——incident X-ray wavelength, 0.15406nm; β——half-height width of the diffraction peak, unit: rad; θ——diffraction angle, unit: degree.
[0096] The specific surface areas of the first carbon matrix, the second carbon matrix, the third carbon matrix and the silicon-carbon composite material have well-known meanings in the art and can be detected by known methods. For example, the specific surface area is tested using a gas adsorption method in accordance with the GB / T19587-2017 test standard, specifically as follows: the object to be tested is taken as a sample, the sample tube is immersed in liquid nitrogen at -196°C, and the adsorption amount of nitrogen on the solid surface at different pressures is measured at a relative pressure of 0.05-0.30, and the adsorption amount of the sample monolayer is obtained based on the BET multilayer adsorption theory and its formula, thereby calculating the specific surface area of the solid.
[0097] The average pore size, micropore volume, and percentage of micropore volume to total pore volume of the carbon matrix have well-known meanings in the art and can be detected by known methods. For example, the pore size is tested by gas adsorption method according to GB / T19587-2017 & GB / T21650.2-2008 test standards, as follows: The porous material sample tube is immersed in -196°C liquid nitrogen, and nitrogen is adsorbed on the material to be tested at a relative pressure of 0-1. The pore size distribution of the porous material is characterized based on the relationship between the volume of each pore size (i.e., pore volume) and the corresponding partial pressure, and the average pore size of the carbon substrate is obtained.
[0098] Dv90, Dv50 and Dv10 of the silicon-carbon composite material have the meanings known in the art, that is, the particle sizes corresponding to the cumulative particle size distributions of 90%, 50% and 10% respectively on a volume basis, which can be detected by known methods. For example, using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000), according to the particle size distribution laser diffraction method GB / T19077-2016, the particle size distribution is measured to obtain Dv90, Dv50 and Dv10.
[0099] The mass percentage of silicon in the first silicon-carbon composite particle, the second silicon-carbon composite particle, the third silicon-carbon composite particle and the silicon-carbon composite material has a well-known meaning in the art and can be detected by known methods. For example, the mass percentage of silicon is determined using an emission spectroscopy test (Inductively coupled plasma, ICP), specifically as follows: take the material to be tested as a sample, digest the sample with aqua regia and hydrofluoric acid HF, test the silicon content of the solution after digestion, and calculate the mass percentage of silicon in the silicon-carbon composite material.
[0100] The porosity of the silicon-carbon composite material has a well-known meaning in the art and can be detected by known methods. For example, according to the GB / T24586 test standard, the porosity P = (V2-V1) / V2*100%, the apparent volume V2 = S*H*A, where: S is the area, the unit is cm 2 ; H is the thickness, in cm; A is the number of samples, in EA; V1 is the true volume of the sample, in cm 3 ; V2 is the apparent volume of the sample, in cm 3 ; The calculation method of the sample true volume V1 is as follows: place the above sample in a true density tester (Accu Pyc II 1340 analyzer), seal the test system, and introduce helium according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, and then according to the ideal gas state equation (v=nRT / P), the gas volumes of the sample chamber and the expansion chamber are obtained respectively, thereby obtaining the gas volume displaced by the sample under certain temperature and pressure conditions, which is the true volume V1 of the sample.
[0101] The powder resistivity of the silicon-carbon composite material has a well-known meaning in the art and can be detected by known methods. For example, the four-probe method can be used, specifically referring to GB / T30835-1994, and the powder resistance tester (ST2722-SZ) is used for measurement: a certain amount of sample powder to be tested is placed in a special mold, and different pressures are set to obtain the powder resistivity under a certain pressure. In this application, the pressure can be 16MPa.
[0102] The powder compaction density of the third carbon matrix and silicon-carbon composite material at different pressures has a meaning known in the art, and the powder compaction density can be measured by using methods known in the art. For example, according to GB / T 24533-2009, an electronic pressure testing machine (such as UTM7305) can be used for testing: a specific amount of powder is placed in a dedicated compaction mold, different pressures are set, and the powder thickness at different pressures is read on the device, and the compaction density at different pressures is obtained by calculation. In the present application, the pressure can be 49000N.
[0103] The tap density of the silicon-carbon composite material has a meaning known in the art, and the powder compaction density can be measured by using methods known in the art. For example, it can be measured using a powder tap density tester with reference to GB / T 5162-2006. The test instrument can be Dandong Better BT-301, and the test parameters are as follows: vibration frequency 250±15 times / minute, amplitude 3±0.2mm, vibration number 5000 times, and measuring cylinder 25mL.
[0104] In some embodiments, the first silicon-carbon composite particles can be prepared by the following method: at 350-800°C, a silicon source gas and a protective gas with a gas flow ratio of 1:1-6 are used for vapor deposition on a first carbon substrate for 8-15 hours, so that the first silicon-based material is deposited in the pore structure of the first carbon substrate to obtain the first silicon-carbon composite particles.
[0105] It should be noted that the first silicon-carbon composite particles with different specifications can be obtained by adjusting the gas flow ratio, deposition temperature and deposition time within the above range, and using different first carbon substrates. In addition, the first silicon-carbon composite particles are not limited to the above method, and other known methods and conditions can also be used to obtain the first carbon-silicon composite particles.
[0106] In some embodiments, the second silicon-carbon composite particles can be prepared by the following method: at 350-800°C, use a silicon source gas and a protective gas with a gas flow ratio of 1:1-6 to vapor deposit on the second carbon substrate for 6-12 hours, so that the second silicon-based material is deposited in the pore structure of the second carbon substrate to obtain second silicon-carbon composite particles.
[0107] It should be noted that the second silicon-carbon composite particles with different specifications can be obtained by adjusting the gas flow ratio, deposition temperature and deposition time within the above range, and using different second carbon substrates. In addition, the second carbon-silicon composite particles are not limited to those prepared by the above method, and other known methods and conditions can also be used to obtain the second carbon-silicon composite particles.
[0108] In some embodiments, the third silicon-carbon composite particles can be prepared by the following method: at 350-800°C, use a silicon source gas and a protective gas with a gas flow ratio of 1:1-6 to vapor deposit on a third carbon matrix for 3-7 hours, so that a third silicon-based material is deposited in the pore structure of the third carbon matrix to obtain third silicon-carbon composite particles.
[0109] It should be noted that the third silicon-carbon composite particles with different specifications can be obtained by adjusting the gas flow ratio, deposition temperature and deposition time within the above range, and using different third carbon substrates. The third silicon-carbon composite particles are not limited to those prepared by the above method, and other known methods and conditions can also be used to obtain the third silicon-carbon composite particles.
[0110] In some embodiments, the carbon coating on the surface of the first silicon-carbon composite particle, the second silicon-carbon composite particle or the third silicon-carbon composite particle can be prepared by the following method: at 400-800°C, using a carbon source gas and a protective gas with a gas flow ratio of 1:1.5-10 to vapor deposit on a carbon substrate deposited with a silicon-based material for 0.2-2h, so that a carbon coating is deposited on the surface of the carbon substrate deposited with the silicon-based material.
[0111] It should be noted that the carbon coating layer is not limited to being prepared by the above method, and the carbon coating layer can also be obtained by using other known methods and conditions.
[0112] In some embodiments, the silicon source gas includes, but is not limited to, at least one of silane-containing hydrocarbons such as silane, dichlorosilane, trichlorosilane, and tetrachlorosilane.
[0113] In some embodiments, the protective gas includes, but is not limited to, at least one of nitrogen, argon, and hydrogen.
[0114] In some embodiments, the carbon source gas includes but is not limited to at least one of hydrocarbon gases such as methane, ethylene, and acetylene.
[0115] In some embodiments, the silicon-carbon composite material can be obtained by the following method: mixing first silicon-carbon composite particles, second silicon-carbon composite particles, and third silicon-carbon composite particles in a certain mass ratio to obtain the silicon-carbon composite material.
[0116] It is understandable that silicon-carbon composite materials of different specifications can be obtained by adjusting the types and mass ratios of the first silicon-carbon composite particles, the second silicon-carbon composite particles, and the third silicon-carbon composite particles.
[0117] In some embodiments, the negative electrode active material may further include graphite.
[0118] Secondary battery
[0119] In a second aspect, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode collector and a negative electrode film layer, the negative electrode film layer comprising a negative electrode active material, and the negative electrode active material comprises the negative electrode active material according to any embodiment of the first aspect.
[0120] According to the present application, the negative electrode plate in the battery includes the negative electrode active material of any embodiment of the first aspect, so the secondary battery has the beneficial effects of the first aspect.
[0121] [Negative electrode]
[0122] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0123] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0124] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0125] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0126] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0127] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0128] Typically, the battery also includes a positive electrode, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode and the negative electrode. The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The separator is set between the positive electrode and the negative electrode, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0129] [Positive electrode]
[0130] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.
[0131] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0132] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0133] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0134] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0135] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0136] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0137] [Electrolytes]
[0138] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0139] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0140] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0141] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0142] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0143] [Isolation film]
[0144] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0145] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0146] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0147] In some embodiments, a secondary battery may include a battery cell including the above-described electrode assembly.
[0148] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0149] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0150] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0151] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0152] In some embodiments, the secondary battery may further include a case; the battery cells are accommodated in the case.
[0153] The battery may include one or more battery cells, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery.
[0154] Furthermore, in the above-mentioned secondary battery, a plurality of battery cells are assembled to form a battery module. Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0155] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0156] Figure 4 and Figure 5 1 is a secondary battery 1 as an example. Figure 4 and Figure 5 The secondary battery 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0157] Electrical devices
[0158] In a fifth aspect, the present application further provides an electrical device, comprising a secondary battery according to any embodiment of the second aspect.
[0159] The battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0160] As the electrical device, the secondary battery mentioned above can be selected according to its usage requirements.
[0161] Figure 6 The power consumption device is taken as an example, and the power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle.
[0162] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a battery including only a battery cell may be used as a power source.
[0163] Example
[0164] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0165] Preparation Example 1-1 :
[0166] Hard carbon is used as the carbon matrix, wherein the pore volume of the micropores of the hard carbon substrate is 0.72 cm 3 / g, average pore size is 3.2nm, specific surface area is 1870m 2 / g.
[0167] The above-mentioned hard carbon substrate was vapor deposited on the hard carbon substrate at 455°C using silane and nitrogen with a gas flow ratio of 1:5 for 10 hours; then at 660°C, ethylene and nitrogen with a gas flow ratio of 1:2 were vapor deposited on the hard carbon substrate for 0.5 hours to form a carbon coating layer, thereby obtaining silicon-carbon composite particles with a silicon content of 55%.
[0168] The corresponding silicon-carbon composite particles are obtained by controlling the type of carbon matrix, gas flow ratio, deposition temperature and deposition time.
[0169] The carbon substrate parameters and deposition processes of Preparation Examples 1-2, 2-1, and 2-2 are detailed in Table 1.
[0170] Table 1
[0171]
[0172] Preparation Example 3-1 :
[0173] Hard carbon is used as the carbon matrix, wherein the specific surface area of the hard carbon substrate is 1200m 2 / g, the average pore size is 2.1nm, the porosity is 82%, and the compaction density of the hard carbon substrate tested under a pressure of 49000N is 0.61g / cm 3 .
[0174] The above-mentioned hard carbon substrate was vapor deposited on the hard carbon substrate at 465°C using silane and nitrogen with a gas flow ratio of 1:6 for 3.5 hours; then at 660°C, ethylene and nitrogen with a gas flow ratio of 1:2 were vapor deposited on the first carbon substrate for 0.5 hours to form a carbon coating layer, thereby obtaining silicon-carbon composite particles with a silicon content of 25%.
[0175] By controlling the type of carbon matrix, gas flow ratio, deposition temperature and deposition time, different silicon-carbon composite particles can be obtained.
[0176] The carbon matrix parameters and deposition process of Preparation Example 3-2 are detailed in Example Table 2.
[0177] Table 2
[0178]
[0179] Example 1
[0180] 1) Preparation of negative electrode sheet
[0181] A silicon-carbon composite material (the silicon-carbon composite particles of Preparation Example 1-1 and Preparation Example 2-1 are mixed in a mass ratio of 5:95), artificial graphite, conductive carbon black, a binder styrene-butadiene rubber (SBR), and a thickener sodium carboxymethyl cellulose (CMC-Na) are fully stirred and mixed in a deionized water solvent system in a mass ratio of 20:75:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; and then dried, cold pressed, and cut to obtain a negative electrode sheet.
[0182] 2) Preparation of positive electrode
[0183] The positive electrode active material Li(Ni 0.8 Co 0.1 Mn 0.1 )O2, conductive carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 96:2:2 to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; and then dried, cold pressed, and cut to obtain a positive electrode sheet.
[0184] 3) Preparation of electrolyte
[0185] In an argon atmosphere glove box (H2O content <0.1ppm, O2 content <0.1ppm), lithium hexafluorophosphate LiPF6 was dissolved in a mixed system of organic solvents ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of the two was 3:7), and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L. Then FEC was added, and the content of FEC was 5% of the total mass of the electrolyte.
[0186] 4) Isolation film
[0187] Polypropylene (PP) film is used as the isolation film.
[0188] 5) Preparation of batteries
[0189] The positive electrode sheet, the isolation film, and the composite negative electrode sheet are stacked in order, with the isolation film placed between the positive and negative electrode sheets to isolate the positive and negative electrode sheets. The electrode assembly is wound and placed in an outer package. The electrolyte is then injected. After standing, cold pressing, forming, shaping and other processes, a lithium-ion secondary battery is prepared.
[0190] Embodiment 2 to Embodiment 9
[0191] The preparation method is similar to that of Example 1, except that different mass percentages and different types of silicon-carbon composite particles are mixed to obtain the silicon-carbon composite material. The specific parameters are shown in Table 3.
[0192] Comparative Example 1
[0193] The preparation method is similar to that of Example 1, except that only the silicon-carbon composite particles of Preparation Example 2-1 are used as the silicon-carbon composite material. The specific parameters are shown in Table 3.
[0194] Comparative Example 2
[0195] The preparation method is similar to that of Example 1, except that only the silicon-carbon composite particles of Preparation Example 1-1 are used as the silicon-carbon composite material. The specific parameters are shown in Table 3.
[0196] In addition, the silicon-carbon composite materials and lithium-ion secondary batteries obtained in Examples 1 to 9 and Comparative Examples 1 and 2 were subjected to performance tests. The test results are shown in Table 3.
[0197] 1. Material capacity test
[0198] Making a button cell battery:
[0199] The silicon-carbon composite material, conductive carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) prepared above are fully stirred and mixed in a deionized water solvent system according to a mass ratio of 95:2:2:1 to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and then dried and cold pressed to obtain a negative electrode plate; then a metal lithium sheet is used as a counter electrode and a polypropylene (PP) film is used as an isolation membrane to assemble a CR2430 button battery in an argon-protected glove box, wherein the formula of the electrolyte is as follows: in an argon atmosphere glove box (H2O content <0.1ppm, O2 content <0.1ppm), a lithium salt lithium hexafluorophosphate LiPF6 is dissolved in a mixed system of organic solvents ethylene carbonate (EC) and diethyl carbonate (DEC) (the volume ratio of the two is 3:7), and stirred evenly to obtain an electrolyte with a lithium salt concentration of 1 mol / L.
[0200] Test process: Under room temperature conditions, the button battery is left to stand for 3 hours, then discharged at a constant current of 0.05C to a voltage of 0.005V, further discharged at a constant current of 50μA to a voltage of 0.005V, left to stand for 5 minutes, and then charged at a rate of 0.1C to a voltage of 0.8V. The capacity at this time is recorded as the de-lithiation capacity, which is the 0.8V capacity of the silicon-carbon composite material.
[0201] 2. Battery cycle life test
[0202] (1) 25℃ Cyclic Performance Test
[0203] Test conditions: At 25°C, the battery was left to stand for 30 minutes, then charged at a rate of 0.5C to a voltage of 4.2V, further charged at a constant voltage of 4.2V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a rate of 0.5C to a voltage of 2.8V. This is a charge and discharge cycle. The discharge capacity was recorded at each cycle.
[0204] Capacity retention rate after n cycles (%)=(discharge capacity at the nth cycle / discharge capacity at the first cycle)×100%.
[0205] (2) 45℃ Cyclic Performance Test
[0206] Test conditions: At 45°C, the battery was left to stand for 30 minutes, then charged at a rate of 1C to a voltage of 4.2V, further charged at a constant voltage of 4.2V to a current of 0.05C, left to stand for 5 minutes, and then discharged at a rate of 1C to a voltage of 2.8V. This is a charge and discharge cycle process, and the discharge capacity is recorded for each cycle.
[0207] Capacity retention rate (%) of the secondary battery after n cycles=(discharge capacity at the nth cycle / discharge capacity at the first cycle)×100%.
[0208] 3. Expansion test
[0209] Take the negative electrode sheets and secondary batteries prepared in the above embodiments and comparative examples.
[0210] Test process: record the thickness T0 of the negative electrode sheet after cold pressing of each embodiment and comparative example; charge the batteries of each embodiment and comparative example at a rate of 0.5C to a voltage of 4.2V, disassemble the negative electrode sheet at this time, and test the thickness of the negative electrode sheet again, and record it as T1. The expansion formula of the sheet is as follows:
[0211] Pole expansion rate (%) = (T1-T0) / T0×100%.
[0212]
[0213]
[0214] According to Table 2, the higher the number of cycles of the lithium-ion secondary battery obtained in each embodiment and comparative example, the better the cycle performance of the corresponding silicon-carbon composite material. The silicon-carbon composite material obtained in each embodiment has better cycle performance than that in comparative example 1. The silicon-carbon composite materials in comparative examples 1 and 2 contain only one type of silicon-carbon composite particles. The mass percentage of silicon element in the silicon-carbon composite particles in comparative example 2 is higher. Although its gram capacity increases accordingly, its cycle performance deteriorates significantly, and it leads to a higher expansion rate of the pole piece.
[0215] According to Examples 1 to 3 and Comparative Example 1, by adding a certain amount of silicon-carbon composite particles with a higher silicon content, the gram capacity of the material can be increased while improving the cycle performance without significantly worsening the expansion of the pole piece.
[0216] According to Examples 4 to 6, the ratio of the mass percentage of silicon elements in different silicon-carbon composite particles in the silicon-carbon composite material has a certain influence on the performance of the silicon-carbon composite material. When 1.06≤ω1 / ω2≤1.6, the silicon-carbon composite material has better cycle performance and a smaller expansion rate.
[0217] According to Examples 1 and 7 to 9, further adding a certain amount of silicon-carbon composite particles with a lower silicon content can further improve the cycle performance of the silicon-carbon composite material and reduce its expansion rate.
[0218] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A negative electrode active material, characterized in that: A silicon-carbon composite material includes a first silicon-carbon composite particle and a second silicon-carbon composite particle; The first silicon-carbon composite particles include a first carbon matrix having a pore structure and a first silicon-based material disposed in the pore structure of the first carbon matrix; The second silicon-carbon composite particles include a second carbon matrix having a pore structure and a second silicon-based material disposed in the pore structure of the second carbon matrix; Furthermore, the mass percentage of silicon in the first silicon-carbon composite particles is greater than the mass percentage of silicon in the second silicon-carbon composite particles.
2. The negative electrode active material according to claim 1, characterized in that The mass percentage of silicon in the first silicon-carbon composite particles is ≥50%, and can be 50%-60%; and / or, The mass percentage of silicon element in the second silicon-carbon composite particles is ≤47%, and can be optionally 38%-47%.
3. The negative electrode active material according to claim 1 or 2, characterized in that: The mass percentage of silicon in the first silicon-carbon composite particles is recorded as ω1, the mass percentage of silicon in the second silicon-carbon composite particles is recorded as ω2, and the negative electrode active material satisfies: 1.06≤ω1 / ω2≤1.6, which can be selected as 1.1-1.
3.
4. The negative electrode active material according to any one of claims 1 to 3, characterized in that: The first carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the first carbon matrix is V1≥0.6cm 3 / g, optional 0.6-0.75cm 3 / g; and / or, The second carbon matrix includes a microporous structure, and the pore volume of the microporous structure in the second carbon matrix is V2≥0.4cm 3 / g, optional 0.5-0.7cm 3 / g.
5. The negative electrode active material according to any one of claims 1 to 4, characterized in that: The first carbon matrix and the second carbon matrix both include a microporous structure, and a pore volume of the microporous structure in the first carbon matrix is greater than a pore volume of the microporous structure in the second carbon matrix.
6. The negative electrode active material according to any one of claims 1 to 5, characterized in that: The average pore size of the pore structure in the first carbon matrix is d1≤5nm, and can be 1-4nm; and / or, The average pore diameter of the pore structure in the second carbon matrix is d2≤10 nm, and can be 3-5 nm.
7. The negative electrode active material according to any one of claims 1 to 6, characterized in that: The average pore size of the pore structure of the first carbon matrix is smaller than the average pore size of the pore structure of the second carbon matrix.
8. The negative electrode active material according to any one of claims 1 to 7, characterized in that: The specific surface area of the first carbon matrix is BET1≥1800m 2 / g, optional 1800-2000m 2 / g; and / or, The specific surface area of the second carbon matrix is BET2≥1600m 2 / g, optional 1600-1800m 2 / g.
9. The negative electrode active material according to any one of claims 1 to 8, characterized in that: The specific surface area of the first carbon matrix is greater than the specific surface area of the second carbon matrix.
10. The negative electrode active material according to any one of claims 1 to 9, characterized in that: Based on the silicon-carbon composite material, a mass content of the first silicon-carbon composite particles is less than a mass content of the second silicon-carbon composite particles.
11. The negative electrode active material according to any one of claims 1 to 10, characterized in that: Based on the silicon-carbon composite material, the mass content of the first silicon-carbon composite particles is ≤10%, and can be optionally 0.1%-5%; and / or, Based on the silicon-carbon composite material, the mass content of the second silicon-carbon composite particles is ≥80%, and can be optionally 80%-99.8%.
12. The negative electrode active material according to any one of claims 1 to 11, characterized in that: At least part of the surface of the first silicon-carbon composite particle and / or the second silicon-carbon composite particle has a coating layer, and optionally, the coating layer is a carbon coating layer.
13. The negative electrode active material according to any one of claims 1 to 12, characterized in that: The silicon-carbon composite material also includes third silicon-carbon composite particles, which include a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the mass percentage of silicon element in the third silicon-carbon composite particles is less than the mass percentage of silicon element in the first silicon-carbon composite particles, and the mass percentage of silicon element in the third silicon-carbon composite particles is less than the mass percentage of silicon element in the second silicon-carbon composite particles.
14. The negative electrode active material according to any one of claims 1 to 13, characterized in that: The silicon-carbon composite material also includes third silicon-carbon composite particles, the first silicon-carbon composite particles include a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the average pore diameter of the pore structure in the third carbon matrix is smaller than the average pore diameter of the pore structure in the first carbon matrix, and the average pore diameter of the pore structure in the third carbon matrix is smaller than the average pore diameter of the pore structure in the second carbon matrix.
15. The negative electrode active material according to any one of claims 1 to 14, characterized in that: The silicon-carbon composite material also includes third silicon-carbon composite particles, the first silicon-carbon composite particles include a third carbon matrix having a pore structure and a third silicon-based material arranged in the pore structure of the third carbon matrix, the specific surface area of the third carbon matrix is smaller than the specific surface area of the first carbon matrix, and the specific surface area of the third carbon matrix is smaller than the specific surface area of the second carbon matrix.
16. The negative electrode active material according to any one of claims 13 to 15, characterized in that: The third silicon-carbon composite particles satisfy at least one of the following conditions: 1) The mass percentage of silicon in the third silicon-carbon composite particles is ≤25%, and can be 20%-25%; 2) The average pore diameter of the pore structure in the third carbon matrix is d3≤4nm, which can be 1-3nm; 3) The third carbon matrix comprises micropores with a pore size of less than 2 nm, wherein the percentage of the micropore volume to the total pore volume is p≥60%, which may be 70%-85%; 4) The powder compaction density of the third carbon matrix under a pressure of 49000N is 0.4-1.1g / cm 3 , preferably 0.4-0.8g / cm 3 ; 5) The specific surface area of the third carbon matrix BET3 ≥ 1000m 2 / g, preferably 1000-1300m 2 / g.
17. The negative electrode active material according to any one of claims 13 to 16, characterized in that: At least one of the first silicon-based material, the second silicon-based material or the third silicon-based material comprises silicon grains; optionally, a grain size of the silicon grains is less than or equal to 10 nm.
18. The negative electrode active material according to any one of claims 1 to 17, characterized in that: The silicon-carbon composite material satisfies at least one of the following conditions: 1) The specific surface area of the silicon-carbon composite material is less than or equal to 6 m 2 / g, optional ≤4m 2 / g; 2) The volume average particle size Dv50 of the silicon-carbon composite material is 5-15 μm, and can be 5-10 μm; 3) Based on the total mass of the silicon-carbon composite material, the mass percentage of silicon in the silicon-carbon composite material is 35%-50%, and can be optionally 40%-50%; 4) The porosity of the silicon-carbon composite material is 45%-65%, and can be optionally 45%-55%; 5) The powder compaction density of the silicon-carbon composite material under a pressure of 49000N is 0.8-1.2g / cm 3 , optional 0.9-1.1g / cm 3 ; 6) The tap density of the silicon-carbon composite material is 0.6-1.0 g / cm 3 , optional 0.7-0.9g / cm 3 ; 7) The powder resistivity of the silicon-carbon composite material is ≤5Ω·cm, and can be ≤3Ω·cm; 8) The silicon-carbon composite material has a value of (Dv90-Dv10) / Dv50≤5, and can be selected to be ≤2.
5.
19. A secondary battery, characterized in that: It comprises a negative electrode plate, wherein the negative electrode plate comprises a negative electrode current collector and a negative electrode film layer, wherein the negative electrode film layer comprises a negative electrode active material, and wherein the negative electrode active material comprises the silicon-carbon composite material according to any one of claims 1 to 18.
20. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 19.
Citation Information
Patent Citations
A lithium ion battery anode active material, a preparing method thereof, an anode and a lithium ion battery
CN104518207A
Negative pole piece, electrochemical device comprising negative pole piece and electronic device
CN114144909A
Silicon-carbon composite material and preparation method thereof, negative active material, negative pole piece, secondary battery and power utilization device
CN116387493A
Silicon-carbon composite material, preparation method thereof, negative electrode and battery
CN117088375A
Lithium-ion cell with high energy density and active anode material for it
DE102020121545A1